China : Competing in the Global Economy - Tseng, Wanda (International Monetary Fund, 2003)
China's economic reforms over the past two decades have brought tremendous economic transformation, rapid growth, and closer integration into the global economy. Real income per capita has increased fivefold, raising millions of Chinese out of poverty. Despite these achievements, difficult reforms--involving the state-owned enterprises and the financial sector--must still be completed, and social pressures from rising unemployment and income inequalities need to be addressed. China's accession to the World Trade Organization will bring benefits but will also impose obligations on the economy, and could prove to be a watershed for the reform process. This book looks at the country's reform process, its past successes and future challenges.